Intestinal estrogen receptor beta suppresses colon inflammation and tumorigenesis in both sexes. (1st November 2020) - Hases, Linnea; Indukuri, Rajitha; Birgersson, Madeleine; Nguyen-Vu, Trang; Lozano, Rodrigo; Saxena, Ashish; Hartman, Johan; Frasor, Jonna; Gustafsson, Jan-Åke; Katajisto, Pekka; Archer, Amena; Williams, Cecilia
Abstract: Estrogen hormones protect against colorectal cancer (CRC) and a preventative role of estrogen receptor beta (ERβ) on CRC has been supported using full knockout animals. However, it is unclear through which cells or organ ERβ mediates this effect. To investigate the functional role of intestinal ERβ during colitis-associated CRC we used intestine-specific ERβ knockout mice treated with azoxymethane and dextran sodium sulfate, followed by ex vivo organoid culture to corroborate intrinsic effects. We explored genome-wide impact on TNFα signaling using human CRC cell lines and chromatin immunoprecipitation assay to mechanistically characterize the regulation of ERβ. Increased tumor formation in males and tumor size in females was noted upon intestine-specific ERβ knockout, accompanied by enhanced local expression of TNFα, deregulation of key NFκB targets, and increased colon ulceration. Unexpectedly, we noted especially strong effects in males. We corroborated that intestinal ERβ protects against TNFα-induced damage intrinsically, and characterized an underlying genome-wide signaling mechanism in CRC cell lines whereby ERβ binds to cis-regulatory chromatin areas of key NFκB regulators. Our results support a protective role of intestinal ERβ against colitis-associated CRC, proposing new therapeutic strategies. Graphical abstract: Schematic illustration; proposed model for ERβ attenuated CRC development. Intestinal epithelial ERβ reduces TNFα signaling through chromatin binding and direct regulation of key p65 modulators and target genes, suppressing the expression of Bcl3 and Birc3, and upregulating Atf3, leading to suppression of the NFκB signaling pathway and thereby reducing inflammation. In vivo this results in less production of CCL2 and CCL4, thereby less recruitment of pro-inflammatory TNFα-secreting macrophages, and reduced tumor development. Image 1 Highlights: Intestinal ERβ protect against colitis-associated adenomas in both sexes. The proposed mechanism involves a crosstalk between ERβ and the TNFα/NFκB signaling pathway. ERβ directly binds and repress the NFκB activators, BIRC3 and BCL3, while upregulating the NFκB inhibitor ATF3. Our data support that an ERβ agonist can be a suitable preventive approach for colitis-induced CRC in both sexes.